2014
DOI: 10.3390/molecules19068027
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Trichoderma harzianum α-Amylase on Treated Wool: Optimization and Characterization

Abstract: α-Amylase from Trichoderma harzianum was covalently immobilized on activated wool by cyanuric chloride. Immobilized α-amylase exhibited 75% of its initial activity after 10 runs. The soluble and immobilized α-amylases exhibited maximum activity at pH values 6.0 and 6.5, respectively. The immobilized enzyme was more thermally stable than the soluble one. Various substrates were hydrolyzed by immobilized α-amylase with high efficiencies compared to those of soluble α-amylase. The inhibition of the immobilized α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 36 publications
6
25
0
Order By: Relevance
“…This change in pH after immobilization may be due to the structural and conformational stability of amylase within the microenvironment of the glass tube matrix. Similar results have been described for porcine pancreas amylase immobilized on functionalized glass beads [21]. In this case, the authors demonstrated that the change in the optimal pH was due to a strong interaction between the enzyme and the support affecting its conformation.…”
Section: Properties Of the Immobilized A-amylasesupporting
confidence: 80%
See 1 more Smart Citation
“…This change in pH after immobilization may be due to the structural and conformational stability of amylase within the microenvironment of the glass tube matrix. Similar results have been described for porcine pancreas amylase immobilized on functionalized glass beads [21]. In this case, the authors demonstrated that the change in the optimal pH was due to a strong interaction between the enzyme and the support affecting its conformation.…”
Section: Properties Of the Immobilized A-amylasesupporting
confidence: 80%
“…In this context, design of a suitable amylase immobilization process and optimization of its operating conditions are very important for industrial applications [7]. a-Amylase has been immobilized on a wide variety of organic and inorganic supports using different methods [13][14][15][16][17][18][19][20][21]. The methods used can be divided into three categories: binding to a support (carrier), entrapment (encapsulation), and crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption peaks at 1392 cm −1 , 1644 cm −1 and at 1743 cm −1 correspond to the stretching vibrations of the CN, CO and CO‐NH 2 , respectively. The peaks around 2900 cm −1 can be caused by the symmetric and antisymmetric stretching vibrations of C‐H aliph groups in CEL . The spectrum of GO‐CEL‐E/N‐GA‐GOD shows the band characteristics associated with the amide group, mainly the occurrence of 1658 cm −1 (CO), 3100–3500 cm −1 (NH stretching), 1550–1640 cm −1 (NH bending), 1458 cm −1 (CN stretching) has indicated covalent attachment GOD …”
Section: Resultsmentioning
confidence: 99%
“…The peaks around 2900 cm −1 can be caused by the symmetric and antisymmetric stretching vibrations of C-H aliph groups in CEL. [26][27][28] The spectrum of GO-CEL-E/N-GA-GOD shows the band characteristics associated with the amide group, mainly the occurrence of 1658 cm −1 (C O), 3100-3500 cm −1 (N-H stretching), 1550-1640 cm −1 (N-H bending), 1458 cm −1 (C-N stretching) has indicated covalent attachment GOD. 29,30 The morphology of the GO sample was characterized using AFM ( Fig.…”
Section: Characterization Of the Carrier And The Immobilized Enzymesmentioning
confidence: 99%
“…In the starch processing industry, α‐amylase is used to hydrolyze α‐1,4‐glucosidic linkages in starch macromolecules to produce maltose and larger oligosaccharides. There have been many reports about the immobilization of α‐amylase on different support materials, including alginate beads , glass beads , chitosan beads , mesoporous silica , gelatin , functionalized nano CaCO 3 , DEAE‐cellulose , treated wool , and modified Fe 3 O 4 nanoparticles , used for the hydrolysis of starch. The support materials exert a critical effect on the stability of the immobilized enzyme and the efficiency of enzyme immobilization.…”
Section: Introductionmentioning
confidence: 99%